2020
DOI: 10.1055/s-0040-1701447
|View full text |Cite
|
Sign up to set email alerts
|

CT Validation of Intraoperative Implant Position and Knee Alignment as Determined by the MAKO Total Knee Arthroplasty System

Abstract: Robotic-assisted technology in total knee arthroplasty (TKA) aims to increase implantation accuracy, with real-time data being used to estimate intraoperative component alignment. Postoperatively, Perth computed tomography (CT) protocol is a valid measurement technique in determining both femoral and tibial component alignments. The aim of this study was to evaluate the accuracy of intraoperative component alignment by robotic-assisted TKA through CT validation. A total of 33 patients underwent TKA using the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 5 publications
2
35
1
Order By: Relevance
“…Several studies assessed the accuracy and the reproducibility of robotic-assisted surgery [42][43][44][45][46]. Sires and Wilson performed CT scans postoperatively to assess the precision of the image-based robotic-assisted TKA and found that 93% of the surgical measurements were 3°of the CT measures postoperatively [46]. The use of preoperative CT scanning and the planning accuracy of robotic-assisted TKA resulted in well-balanced knees [47].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies assessed the accuracy and the reproducibility of robotic-assisted surgery [42][43][44][45][46]. Sires and Wilson performed CT scans postoperatively to assess the precision of the image-based robotic-assisted TKA and found that 93% of the surgical measurements were 3°of the CT measures postoperatively [46]. The use of preoperative CT scanning and the planning accuracy of robotic-assisted TKA resulted in well-balanced knees [47].…”
Section: Resultsmentioning
confidence: 99%
“…Some previous studies have relied on the robot's optical tracking system to quantify resection accuracy [14,16,18e20], which neglects potentially significant errors in the registration process [23]. Other studies use preoperative and postoperative CT scans to measure resection or implant alignment angles [11,17], which allow independent quantification of the system accuracy and reduce uncertainty in establishing anatomic coordinate systems. Limitations in the CT slice thickness induce errors in segmentation of the resection surfaces which are commonly parallel to the axial slices.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, implant-induced metal artifacts cause uncertainty in alignment measures [24,25]. A study by Sires and Wilson [17] found absolute differences between resection angles measured intraoperatively and the corresponding implant alignments measured using a CT scan ranged from 1.09 ± 0.75 to 1.97 ± 1.41 for tibial coronal and sagittal alignment, respectively, with 9% of the accuracy measurements deviating by >3 . The small differences between resection angles and implant angles observed in our study suggest that much of this error may be attributed to the anatomic registration step in the RATKA workflow.…”
Section: Discussionmentioning
confidence: 99%
“…Several robotic-assisted TKA systems, including CASPAR, Tsolution, ROSA, ROBODOC and Mako, have been implemented into clinical application [ [25] , [26] , [27] , [28] ]. Previous studies showed that robotic-assisted TKA can offer more accurate bone cuts, precise placement of implants and provide balanced extension and flexion gaps [ 29 , 30 ]. Moreover, robotic-assisted TKA can reduce the extent of bone resection and damage to the soft tissue, which are associated with postoperative pain [ 31 ].…”
Section: Introductionmentioning
confidence: 99%